2018
DOI: 10.1111/jeb.13345
|View full text |Cite
|
Sign up to set email alerts
|

Independent and interactive effects of immune activation and larval diet on adult immune function, growth and development in the greater wax moth (Galleria mellonella)

Abstract: Organisms in the wild are likely to face multiple immune challenges as well as additional ecological stressors, yet their interactive effects on immune function are poorly understood. Insects are found to respond to cues of increased infection risk by enhancing their immune capacity. However, such adaptive plasticity in immune function may be limited by physiological and environmental constraints. Here, we investigated the effects of two environmental stressors - poor larval diet and an artificial parasite-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 81 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…In this study, we investigated the specific immune responses of oriental armyworms fed different P:C artificial diets following bacteria challenge. Studies have generally found that there are nutrient-biased trade-offs between immune traits and life history traits, such as growth and longevity [ 11 , 32 , 34 ]. Individuals that ingested a low-nutrition diet developed more slowly, but they possessed stronger immunity, because they had to invest more energy into coping with more immune challenges which they are likely to encounter during their longer lifespan [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated the specific immune responses of oriental armyworms fed different P:C artificial diets following bacteria challenge. Studies have generally found that there are nutrient-biased trade-offs between immune traits and life history traits, such as growth and longevity [ 11 , 32 , 34 ]. Individuals that ingested a low-nutrition diet developed more slowly, but they possessed stronger immunity, because they had to invest more energy into coping with more immune challenges which they are likely to encounter during their longer lifespan [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diets that are high or low in nutrition without identifying the key nutritional element also affect the insect’s immune traits. For example, the greater wax moth Galleria mellonella larvae and adults that emerged from the larvae reared on a low-nutrition diet exhibited a stronger encapsulation response than those on a high-nutrition diet [ 11 , 32 ]. Studies also revealed that a change in the relative amount of protein and carbohydrate in the diet could affect specific immune responses and survival of the infected hosts [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the association between food quantity/quality and health [ 118 ], Galleria larvae have been used to study the impact of (i) a poor-quality diet and (ii) an artificial parasite-like immune challenge on pupal development, growth and adult immunity. A hostile nutritional environment can increase the risk of infection, thus provoking more frequent and robust immune responses, ultimately leading to greater fitness [ 119 ]. Categories of food differing in nutritional quality therefore affect the life history traits of Galleria [ 120 ].…”
Section: Model Insects For Nutrition Researchmentioning
confidence: 99%
“…That is, it is associated with resistance to some parasites/pathogens between species (Nigam et al, 1997). Dietary quality may also affect PO activity (Cotter et al, 2011;Kangassalo et al, 2018). Studies indicate that the food component that affects immunity is the amount of protein in diets (Lee et al, 2008, Singer et al, 2014.…”
Section: Introductionmentioning
confidence: 99%